Mentorship support in the professional practice of future educators and teachers - Amela; Хамидовић, Кимета (Norma, 2026)
Mentorship support in the professional practice of future preschool teachers and school teachers represents a significant factor in the process of initial education, within which theoretical knowledge is connected with practical experiences in a real educational context. Special attention is devoted to the role of mentorship in the planning, organization, and implementation of professional practice, as well as to its contribution to the development of students’ professional competencies. The role of the mentor is reflected in defining learning goals and outcomes, structuring and guiding practical activities, as well as providing continuous support to students throughout the practice process. An important segment of mentoring work relates to providing feedback, encouraging a reflective approach, and fostering the development of professional autonomy. It is concluded that mentorship support contributes to a higher-quality connection between theory and practice, the development of independence and responsibility, as well as the formation of the professional identity of future preschool teachers and school teachers.
Keywords: mentorship; professional practice; professional identity; future preschool and primary school teachers; professional competencies